2018
DOI: 10.1080/02688697.2018.1527012
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of lumbar fusion in patients denied surgical treatment of the sacroiliac joint

Abstract: Purpose. Effective treatment of medical conditions relies on proper diagnosis. Clinical trials show the safety and effectiveness of sacroiliac joint (SIJ) fusion in patients with chronic SI joint dysfunction. To what extent is the condition under recognised? Objective. To determine whether under recognition of SIJ pain affects healthcare trajectories in Spanish patients with low back pain. Methods. Retrospective study of characteristics and consequences of 189 patients with persistent SIJ pain seen in an outpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Previous estimates of up to 30% of chronic back pain being referable to the SI joint have been published by numerous authors. [3][4][5][6][7] Recognition of this pathology has been limited in the past by a lack of clear diagnostic criteria. With increasing focus on this clinical entity, there is starting to be more consensus on appropriate means of diagnosing SI joint dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous estimates of up to 30% of chronic back pain being referable to the SI joint have been published by numerous authors. [3][4][5][6][7] Recognition of this pathology has been limited in the past by a lack of clear diagnostic criteria. With increasing focus on this clinical entity, there is starting to be more consensus on appropriate means of diagnosing SI joint dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 While the traditional focus of healthcare providers has been on lumbosacral pathology, sacroiliac joint dysfunction is an underappreciated and underdiagnosed cause of low back pain. Previous studies [3][4][5][6][7][8] have suggested that 15-30% of chronic low back pain is due to pathology located in the sacroiliac joint. Historically, recognition of this pathology was difficult, limited by lack of standardized diagnostic criteria and disease-specific outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Despite this high prevalence, SIJ pain likely remains underdiagnosed, 7 and failure to correctly diagnose SIJ pain may result in unsuccessful surgical procedures on other areas of the body, which do not improve patient quality of life. 8,9 For patients diagnosed with SIJ pain who have insignificant or nondurable responses to conservative measures, surgical treatment with arthrodesis of the SIJ can result in substantial pain relief and improvements in quality of life. 10 A number of minimally invasive (MIS) techniques have emerged that significantly reduce the complexity and morbidity of the operation, and SIJ fusion can often be performed as an outpatient procedure.…”
mentioning
confidence: 99%